The Use of Closure Devices for Aortic Stent-Graft Insertion: Outcomes Following a Paradigm Shift to Percutaneous Access in a Tertiary Vascular Center. (October 2019) - White, Alan D.; Hazar, Can; Jarosz, David; Walker, Paul; Shaw, David; Tingerides, Costa
Background: This retrospective case series aims to evaluate the efficacy of the Perclose ProGlide system for postoperative hemostasis following aortic stent-graft insertion. Material and Methods: A prospectively maintained database of patients with a minimum follow-up of 12 months following percutaneous aortic procedures was interrogated. Preprocedural computed tomography (CT) scans were reviewed to assess existing stenosis in the common femoral artery (CFA). Arteries with an estimated stenosis of greater than 25% on visual inspection underwent quantification using multiplanar and curved planar reformation. The preoperative and 1-year follow-up CTs of these patients were assessed for change in stenosis. Analysis was performed by 2 independent reviewers, with senior authors reviewing any discrepancies. Results: One hundred forty-two endovascular aortic aneurysm repairs (EVARs) were performed. The ProGlide system was used in 235 arteries, yielding a high success rate in obtaining postprocedural hemostasis (94%). There were 13 postprocedural access-related complications, including 5 patients requiring surgical closure due to inadequate seal. Two patients required thrombectomy due to distal embolization. One patient required CFA endarterectomy at 6 months for the treatment of preexisting short distance claudication. Vessel analysis was performed in 31 arteries. Mean preoperative stenosis was 32% (range: 20%-57%). Mean postoperative stenosis was 32% (21%-57%). No significant change in degree of stenosis was detected (defined as a 5% change). Conclusions: The ProGlide system yielded a high success rate in obtaining postoperative hemostasis with low rate of conversion to surgical closure and low complication rates. There was no evidence of worsening vessel stenosis in arteries with preprocedural stenotic disease. Level of Evidence: Level 4, Case Series.